Mediating role of computer experience in the association between MOOC-efficacy and meaningful learning - Razali, Norliza (Human Resource Management Academic Research Society, 2021)
This study examines three critical constructs in twenty-first-century e-education—MOOCefficacy, meaningful learning, and computing experience—among undergraduate students at selected public universities in Malaysia. Its primary purpose is to investigate the mediating function of computer experience in the link between MOOC-efficacy and meaningful learning. This study defines MOOC-efficacy based on four aspects (information searching, making queries, MOOC learning, and MOOC usability). Meanwhile, meaningful learning is conceptualised in five dimensions (i.e.cooperative learning, active learning, authentic learning, constructive learning, and intentional learning). This study incorporated a crosssectional survey design. The data were acquired using a 52-item questionnaire whose reliability indices for the dimensions ranged from 0.822 to 0.890. The study’s population comprises university students with prior experience using MOOCs and volunteered to participate in the study. Simple random selection was used to get a sample of 603 students. The Structural Equation Modeling (SEM) test of bootstrapping for mediation was used for data analysis. The findings suggest no evidence of a mediation impact of computer experience on MOOC-efficacy and meaningful learning. The findings add to our understanding of how an open online ecosystem function. This study provides insights that could be used to meet the requirements and preferences of learners. MOOC-efficacy interventions are critical for motivating students to engage in meaningful learning on the e-learning platform.